The Brief Review on the Textile Sensors for the Wearable uses (International Journal of Innovative Research in Engineering & Management, 2023)
Material-based sensors, a new kind of  wearable gadget, may be the next step in the human  body's sensing and control for instantaneous age, utility,  and friendliness. The primary aim of this research is to  give an overview of material-based sensors, sensor  substrates, and substrate pre-handling, which includes  surface modification of the basic substrate. This research  also looks at a variety of popular polymers and inks, as  well as techniques for creating strong conductive strands  or materials, and different variables that influence the  solidity and cleanliness of conductive materials. This first  edition also looks at qualities including adequacy and  execution of material-based sensors that are prone to wear  and tear over time, as well as care, upkeep, and  toughness. During development, this element of  execution (wearing and care) is often overlooked. Wear  and care implications for sensor execution should be  addressed, and steps to prolong the life cycle and  execution of material-based sensors should be taken.
Keywords: Electronics; Material; Sensor; Textile; Wearable